The place of the visual arts in Pre-University education in Ghana - Adjei, Anthony Kwasi (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of the Degree of Master of Arts in Art Education.